Return to sport after lumbar fusion among patients with degenerative spinal disease - Jakub Baranowski; Agata Terebecka; Anna Kuźminko-Bojarczuk; Leszek Sagan (Kazimierz Wielki University, 2022)
Abstract Introduction and purpose Low-back pain (LBP) is one the most common causes of medical visits. Although specific diagnosis cannot always be made, degenerative spinal disease may be one. Non-surgical approach is the treatment of choice in most cases and provides satisfactory results. However, some patients require surgery when conservative treatment fails. Among different interventions, lumbar fusion is one of the most important. Common question arising from patients qualified for this type of surgery is the possibility of returning to sport (RTS). Description of the state of knowledge Successful RTS may be achieved with proper rehabilitation without surgery. However, invasive intervention, including lumbar fusion, is indicated when a non-surgical approach fails. Return to recreational sport is highly plausible among patients operated for spinal structures degeneration. The timing of RTS varies on the type of sport, nonetheless one may expect to rejoin sporting activities within a year. The return to golf has been well documented in the literature in comparison to other sport types. Golfers may expect successful recovery as 79-100% of them re-engage in golfing activities. Positive RTS is feasible for professional athletes and some of them are able to compete at elite level after surgery. The need for a well-structured rehabilitation protocol is underlined. Summary Successful RTS can be achieved in the vast majority of cases after lumbar fusion procedures. The suggested timeframes has been set as 6-12 months depending on the sport type. There are no strict recommendations, but general criterias include: 1) complete/nearly complete pain reduction; 2) adequate flexibility, strength and range of motion; 3) radiographic evidence of successful fusion.